1995
DOI: 10.1017/s0950268800058441
|View full text |Cite
|
Sign up to set email alerts
|

Measles vaccine efficacy during an outbreak in a highly vaccinated population: Incremental increase in protection with age at vaccination up to 18 months

Abstract: SUMMARYDuring a large measles outbreak in Quebec City in 1989, two investigations conducted in parallel evaluated the relative risk of measles and measles vaccine effectiveness with respect to age at vaccination. The study was a school-based case-control study including 563 cases and 1126 classmate controls. The second was a cohort study of the siblings of school cases including 493 siblings aged between 1 and 19 years. The relative risks (RR) of measles were similar in both settings and the trend towards incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The possibility of decreased seroconversion rates and weak responses to vaccine boosting has to be taken into account if infants are vaccinated at an earlier age (37). During a measles outbreak in Quebec in 1989, De Serres et al (10) found a lower rate of vaccine effectiveness in children at 12 months of age (85%) than in older children vaccinated after 15 months of age (94%), but in 1996 they found a 96% rate of effectiveness of vaccination at 6 to 11 months of age during a measles outbreak in a population immunized exclusively by vaccination (11). In 1994, infants from mothers born in the United States after 1961 with low levels of passively acquired measles antibodies were vaccinated at the ages of 9, 12, and 15 months, and they seroconverted at high rates of 92, 97, and 99%, respectively (20).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of decreased seroconversion rates and weak responses to vaccine boosting has to be taken into account if infants are vaccinated at an earlier age (37). During a measles outbreak in Quebec in 1989, De Serres et al (10) found a lower rate of vaccine effectiveness in children at 12 months of age (85%) than in older children vaccinated after 15 months of age (94%), but in 1996 they found a 96% rate of effectiveness of vaccination at 6 to 11 months of age during a measles outbreak in a population immunized exclusively by vaccination (11). In 1994, infants from mothers born in the United States after 1961 with low levels of passively acquired measles antibodies were vaccinated at the ages of 9, 12, and 15 months, and they seroconverted at high rates of 92, 97, and 99%, respectively (20).…”
Section: Discussionmentioning
confidence: 99%
“…Even if a large percentage of the general population is immunised, unless the vaccine is 100% effective a large proportion of infected children will have been immunised. The numbers of immunised and non-immunised children infected in these outbreaks invariably shows that these vaccines have a high efficacy—for example, in an outbreak of measles in Quebec City in 1989 of 62 siblings of children with measles who developed measles themselves, 41 (66%) were immunised 19. This might suggest that the vaccine was not effective, but of 17 unvaccinated siblings all (100%) developed measles, whereas only 41 of 441 (9%) vaccinated siblings did so.…”
Section: Efficacy Of Vaccinesmentioning
confidence: 99%
“…Primary and secondary vaccination failures have been associated with susceptibility et al, 1987;Fine & Zell, 1994;De Serres et al, 1995;Sutcliffe & Rea, 1996;Paunio et al, 2000), whereas naturally immune subjects only rarely become susceptible to subclinical MV reinfection (Muller et al, 1996). It has been speculated that susceptibility to reinfection could be facilitated by genetic differences between the MV vaccine virus and currently circulating wt MV strains (Tamin et al, 1994; Santibanez et al, 2005 Here, we have used the antibody depletion approach to study the relative contribution of H-and F-specific antibodies in sera from naturally immune subjects to VN activity against both MV Edmonston and wt MV.…”
mentioning
confidence: 99%